In situ follicular neoplasia/lymphoma: Three illustrative cases exemplifying unique disease presentations - Uma Sakhadeo; Ashwini Mane; Tanuja Shet (Wolters Kluwer Medknow Publications, 2012)
We report three elderly patients with follicular lymphoma in situ (FLIS) each highlighting a unique pattern of disease presentation and progression. The first patient had incidentally detected FLIS with peripheral blood spill and yet had an 11-year uneventful follow up. The second patient with an overt follicular lymphoma (FL) developed high-grade transformation in jejunum with FLIS extensively involving the Payers patches. The third patient had a FLIS but that qualified as higher grade and was treated in spite of lack of overt FL mainly because of higher grade and patient subsequently did develop overt FL. The first case of typical FLIS confirms that peripheral blood spill does not connote poor prognosis in FLIS, the second case illustrates that FLIS may colonize mucosa-associated lymphoid tissue as part of homing in process of a disseminated FL and the third case validates the aggressive nature of high-grade FLIS.